Halal processed food and beverages: some concerns on food additives and ingredients - Jaswir, Irwandi (TM-Info-Media Sdn. Bhd., 2009)
Islam is not merely a religion of rituals, but is a way of life. Rules and manners from the Islamic teachings govern the life of Muslims: individual and collective level. In Islam, eating is also considered as a matter of ibadah (worship) to God, just like ritual prayers. Muslims follow the Islamic dietary code and foods that meet the code are called halal (lawful, permitted). Muslims are supposed to make an effort to obtain halal food of good quality. On the other hand, for non-Muslim consumers, halal foods often are perceived as specially selected and processed to achieve the highest state of quality.